The essence and role of environmentally friendly agricultural land use in agriculture - Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2021)
The article deals with the relationship between economic development and environmental security.With regard to agricultural land use, ensuring environmental security involves optimizing the organization of land use and land use process on the basis of environmental restrictions on environmental pollution and agricultural products. First of all, according to environmental constraints, the possibilities of exploitation of natural resources and taking into account the peculiarities of agroecosystems (natural and climatic conditions, water resources, terrain, land and soil structure, land erosion, etc.) are determined to address food security. On their basis, ecologically balanced operation of agroecosystems is carried out through the formation of ecologically safe land uses, which provide for the optimization of economic activity of agricultural producers, taking into account environmental constraints. The article clarifies the essence and significance of ecologically safe agricultural land use in agriculture, proposes an approach to defining the essence of ecologically safe agricultural land use as a process of land use in the agricultural sector of the economy, which prevents the danger to human health, degradation of land resources, as well as their resilience to environmental threats and risks. The role of ecologically safe agrarian land use in ensuring sustainable development of rural areas and directions of influence of interaction of ecological and economic components of safety of agrarian land use are defined Keywords. Ecologically safe agricultural land use, agriculture, economic development, sustainable development.